PERANCANGAN SISTEM PAKAR DIAGNOSA PENYAKIT UMUM DAN MENGETAHUI OBAT HERBALNYA MENGGUNAKAN MESIN INFERENSI FORWARD CHAINING BERBASIS WEB-MOBILE - Agung Sasongko (LPPM Universitas Bina Sarana Informatika, 2012)
The development of communication technology world is now very advanced and continues to support human needs. Convenience, practicality, accuracy of information becomes its own needs for the life of modern society today. Information on world health is also needed because of increased awareness about the health of modern life. Needs of a growing economy makes the factor for many people to try a natural treatment with herbal medicine, information on medicinal plants are also more and more. It would be very useful when communications technology was developed to facilitate all the people getting the information about the diagnosis of common diseases and herbal medicinal plants that can be used for treatment through a mobile web application that can be accessed via a gadget that has supported the web-browser without installing the application of ES in their gadgets.Keywords: Expert system, herb, web mobile, common disease